Optimal Analysis of Left Atrial Strain by Speckle Tracking Echocardiography: P‐wave versus R‐wave Trigger. Issue 8 (3rd November 2014) - Hayashi, Shuji; Yamada, Hirotsugu; Bando, Mika; Saijo, Yoshihito; Nishio, Susumu; Hirata, Yukina; Klein, Allan L.; Sata, Masataka
<x xml:space="preserve">Abstract</x> Background Left atrial (LA) strain analysis using speckle tracking echocardiography is useful for assessing LA function. However, there is no established procedure for this method. Most investigators have determined the electrocardiographic R‐wave peak as the starting point for LA strain analysis. To test our hypothesis that P‐wave onset should be used as the starting point, we measured LA strain using 2 different starting points and compared the strain values with the corresponding LA volume indices obtained by three‐dimensional (3D) echocardiography. Methods We enrolled 78 subjects (61 ± 17 years, 25 males) with and without various cardiac diseases in this study and assessed global longitudinal LA strain by two‐dimensional speckle tracking strain echocardiography using EchoPac software. We used either R‐wave peak or P‐wave onset as the starting point for determining LA strains during the reservoir (Rres, Pres), conduit (Rcon, Pcon), and booster pump (Rpump, Ppump) phases. We determined the maximum, minimum, and preatrial contraction LA volumes, and calculated the LA total, passive, and active emptying fractions using 3D echocardiography. Results The correlation between Pres and LA total emptying fraction was better than the correlation between Rres and LA total emptying fraction (r = 0.458 vs. 0.308, P = 0.026). Pcon and Ppump exhibited better correlation with the corresponding 3D echocardiographic parameters than Rcon (r = 0.560 vs. 0.479, P = 0.133) and Rpump (r = 0.577 vs. 0.345, P = 0.003), respectively. Conclusions LA strain in any phase should be analyzed using P‐wave onset as the starting point rather than R‐wave peak.